Becoming an interdisciplinary scientist: an analysis of students' experiences in three computer science doctoral programmes. Issue 4 (3rd July 2016) - Calatrava Moreno, María del Carmen; Danowitz, Mary Ann
ABSTRACT: The aim of this study was to identify how and why doctoral students do interdisciplinary research. A mixed-methods approach utilising bibliometric analysis of the publications of 195 students identified those who had published interdisciplinary research. This objective measurement of the interdisciplinarity, applying the Rao-Stirling index to Web of Science and Scopus citations, allowed for a comparison of students' interdisciplinary research outcomes from three different computer science programmes: a traditional programme, a multidisciplinary doctoral school and an interdisciplinary doctoral college. Applying a sociocultural approach, interviews with the 15 most interdisciplinary students were analysed to understand how dispositions and experiences of students and factors of the different programmes affect the circumstances and processes of becoming an interdisciplinary early career scientist. The data indicate that student motivations, previous skills and knowledge interacted with policies and programme structures including type of funding and supervisor expectations to play a crucial role in interdisciplinarity at the doctoral level. These factors can give rise to interdisciplinary research even in programmes without interdisciplinary focus and compromise the interdisciplinary goals of interdisciplinary programmes.